Integrated Control of Coffee Bean Borer (Hypothenemus Hampei) on Sigararutang Coffee, Motung Village, Ajibata Sub-district, Toba Samosir District, Sumatera Utara - Suswati Suswati; Sumihar Hutapea; Rehia Isabella Barus; Setiawan Setiawan; Ade Prayoga Hutapea (Budapest International Research in Exact Sciences (BirEx) Journal, 2020)
Integrated control Hypothenemus hampei in  Saurdot farmer group, Motung Village, Ajibata District, Toba Samosir Regency, North Sumatra. The purpose of the activity was to increase the knowledge and skills of farmers about H.hampei and their management measures by improving cultivation techniques. The socialization of coffee borer pest management has been carried out by improving crop cultivation through spacing, crop pruning, chemical control and planting refugia plants. Partner problems are overcome by a number of technological solutions, which are carried out using technology transfer methods through education, training, demonstration plots, and mentoring. Socialization activities can increase farmers' knowledge about coffee berry borer (CBB) pests and its environmentally friendly control. The prototype of healthy coffee cultivation is very beneficial in increasing the knowledge and skills of Saurdot farmer group members in coffee cultivation. There is an increase in both knowledge and skills in the application of plant cultivation techniques. coffee specifically about the spacing of coffee seedlings increased by 15.38%, the distance of the shading trees around 50%, the selection of protective trees only about 50%, pruning coffee plants around 54%, pruning of shading trees around 25%, applying basic fertilizer and supplementary fertilizers around 50% in addition, there was also an increase in the group in the introduction of plant pests and control methods. There was an increase in the knowledge of partner groups about the type of pest of coffee plants by 11.11%, CBB pest  by 51.11%, about CBB pest control by 50% and knowledge about the types of pesticides in controlling CBB by 50%